IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MEMBENTUK KEPRIBADIAN PESERTA DIDIK MELALUI PEMBELAJARAN IPS TERPADU KELAS VIII DI MTS MIFTAHUL ULUM NGEMBAL KECAMATAN TUTUR KABUPATEN PASURUAN (Universitas Negeri Semarang, 2023)
MTs Miftahul Ulum Ngembal is a school with thick Islamic teachings. Character education is carried out through school cultural habituation activities and learning activities, one of which is through social science learning. This research utilized the descriptive qualitative method. This study aims 1) Determine the implementation of character education in shaping students’ personalities through social science subject, 2) Discover students’ perception of the implementation of character education, 3) Discover the character assessment carried out by educators in shaping students’ personalities through social science subject. The results of this study indicate 1) The implementation of character education in shaping students’ personalities through integrated social science learning through the stages of planning, implementation, and evaluation. The learning procces is carried out based on preliminary activities, core activities, and closing activities, 2) Students show good responses towards the implementation of character education, 3) Character assessment in shaping students’ personalities is carried out using an attitude assessment sheet consisting of self-assessment, peer-assessment, and assessment based on educator journals. MTs Miftahul Ulum Ngembal adalah sekolah yang kental dengan ajaran agama Islam. Pendidikan karakter dilaksanakan melalui kegiatan pembudayaan sekolah dan kegiatan pembelajaran, salah satunya melalui pembelajaran IPS. Penelitian ini menggunakan metode kualitatif. Penelitian ini bertujuan 1) Mengetahui implementasi pendidikan karakter dalam membentuk kepribadian peserta didik melalui pembelajaran IPS, 2) Mengetahui respon peserta didik adanya implementasi pendidikan karakter, 3) Mengetahui penilaian karakter yang dilakukan oleh pendidik dalam menilai kepribadian peserta didik melalui pembelajaran IPS. Hasil penelitian menunjukkan 1) Implementasi pendidikan karakter dalam membentuk kepribadian peserta didik melalui pembelajaran IPS dilaksanakan berdasarkan tahapan perencanaan, pelaksanaan, dan evaluasi. Proses pembelajaran dilaksanakan melalui kegiatan pendahuluan, inti, dan penutup, 2) Peserta didik menunjukkan respon yang positif adanya implementasi pendidikan karakter, 3) Penilaian karakter dalam membentuk kepribadian dilakukan menggunakan lembar penilaian sikap yang terdiri dari penilaian diri sendiri, penilaian antar teman, dan penilaian berdasarkan jurnal pendidik.